A coating for protecting the surface of samarium cobalt permanent magnet material and a method for protecting the surface of samarium cobalt permanent magnet material
By depositing a tantalum-containing plating layer on the surface of samarium-cobalt permanent magnet material, the problem of magnetic performance attenuation in high-temperature environments is solved, and the high-temperature stability and oxidation resistance of the material are improved.
Patent Information
- Application Number
- CN202110577559.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-05-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-05-26
AI Technical Summary
The long-term working of samarium-cobalt permanent magnet materials in high temperature environments will lead to attenuation of magnetic properties, mainly due to the formation of surface aging layers.
The plating layer containing metal tantalum Ta, tantalum oxide TaOX1, tantalum nitride TaNX2 or its alloy is deposited on the surface of samarium-cobalt permanent magnet material by sputtering, ionic plating or spraying to block the diffusion of internal elements and external oxygen elements.
It effectively improves the high temperature resistance of samarium-cobalt permanent magnet materials, inhibits the attenuation of magnetic properties, and improves the material's oxidation resistance and stability.
Smart Images

Figure CN115410785B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of material technology, and in particular to a coating for protecting the surface of a samarium-cobalt permanent magnet material and a method for protecting the surface of a samarium-cobalt permanent magnet material. Background Art
[0002] In the 1960s, the first generation of rare earth permanent magnet materials, 1:5 type samarium cobalt materials (SmCo5), were born. In the 1970s, the second generation of rare earth permanent magnet materials, 2:17 type samarium cobalt permanent magnet materials (Sm2Co17), appeared. In the 1980s, the third generation of permanent magnet materials represented by neodymium iron boron (Nd-Fe-B) appeared. China is the world's largest country in rare earth raw material reserves and production. After decades of development, the market demand for rare earth permanent magnet materials has prompted the technology to develop in the direction of high performance.
[0003] Samarium cobalt permanent magnet materials are widely used in environments with temperatures above 200°C due to their high comprehensive magnetic properties and excellent temperature resistance. High-performance samarium cobalt permanent magnet materials have been widely used in high-speed rail, new energy vehicle motors, water pumps, sensors and other fields. Low temperature coefficient permanent magnet materials are used in space satellites, aerospace and other fields due to their excellent temperature stability. High temperature resistant samarium cobalt permanent magnet materials can already be used in environments with temperatures of 550°C.
[0004] However, the magnetic properties of samarium cobalt permanent magnet materials will decay when working for a long time in a temperature environment of 350℃. The formation of surface aging layer is the main reason for the attenuation of magnetic properties. Anti-oxidation and high-stability surface protective coating is an effective way to inhibit the formation of surface aging layer.
[0005] Application Contents
[0006] The present application provides a coating for protecting the surface of a samarium cobalt permanent magnet material and a method for protecting the surface of a samarium cobalt permanent magnet material, which can improve the high temperature resistance of the samarium cobalt permanent magnet material.
[0007] In a first aspect, the present application provides a coating for surface protection of samarium cobalt permanent magnet materials, comprising at least one of the following components:
[0008] Tantalum metal Ta;
[0009] Tantalum Oxide TaO X1 , X1 is any number between 0 and 2.5;
[0010] Tantalum Nitride TaN X2 , X2 is any number between 0 and 1.6;
[0011] An alloy comprising metal tantalum Ta and metal M, wherein M comprises at least one of V, Nb, Zr, Hf, Cr, Al, and Ni.
[0012] Among them, samarium cobalt permanent magnet materials include the first generation rare earth permanent magnet material 1:5 type samarium cobalt material (SmCo5), the second generation rare earth permanent magnet material 2:17 type samarium cobalt permanent magnet material (Sm2Co 17 ). In addition to the two basic components of Sm and Co, the above materials also contain one or more of Fe, Cu, Zr, Ti, Si, Sn, Nb, V, Ni, Mo, B and rare earth elements La, Ce, Pr, Nd, Er, Gd, Dy, Ho, Tb, and Eu.
[0013] Tantalum metal Ta has a high melting point, good toughness and excellent chemical stability, making tantalum metal Ta coating an excellent choice for high temperature resistance, friction resistance and extreme chemical corrosion resistance.
[0014] In a further embodiment, the coating comprises one of the following components:
[0015] Tantalum metal Ta;
[0016] Tantalum Oxide TaO X1 , X1 is any number between 0 and 2.5;
[0017] Tantalum Nitride TaN X2 , X2 is any number between 0 and 1.6;
[0018] An alloy comprising metal tantalum Ta and metal M, wherein M comprises at least one of V, Nb, Zr, Hf, Cr, Al, and Ni.
[0019] For example, the coating composition can be metal tantalum Ta, recorded as Ta coating, or tantalum oxide TaO X1 , denoted as TaO X1 Plating.
[0020] In a further embodiment, the alloy is composed of metal tantalum Ta and metal M, and M includes at least one of V, Nb, Zr, Hf, Cr, Al, and Ni.
[0021] For example, the coating may be composed of an alloy, and the alloy may be composed of metal tantalum Ta and metal Nb. In this case, the coating is recorded as a TaNb binary alloy coating. The alloy may also be composed of metal tantalum Ta, metal Zr and metal Hf. In this case, the coating is recorded as a TaZrHf ternary alloy coating.
[0022] In a further embodiment, the coating comprises at least one layer, each layer is stacked, and each layer comprises one of the following components:
[0023] Tantalum metal Ta;
[0024] Tantalum Oxide TaO X1 , X1 is any number between 0 and 2.5;
[0025] Tantalum Nitride TaN X2 , X2 is any number between 0 and 1.6;
[0026] An alloy comprising metal tantalum Ta and metal M, wherein M is at least one of V, Nb, Zr, Hf, Cr, Al, and Ni.
[0027] For example, the number of layers may be one, two, or three.
[0028] In a further embodiment, the composition of each layer is one of the following components:
[0029] Tantalum metal Ta;
[0030] Tantalum Oxide TaO X1 , X1 is any number between 0 and 2.5;
[0031] Tantalum Nitride TaN X2 , X2 is any number between 0 and 1.6;
[0032] An alloy comprising metal tantalum Ta and metal M, wherein M is at least one of V, Nb, Zr, Hf, Cr, Al, and Ni.
[0033] In a further embodiment, the compositions of the layers are different.
[0034] For example, the number of layers may be two, which are respectively recorded as a first layer and a second layer covering the first layer. The composition of the first layer may be tantalum nitride TaN X2 The second layer can be metal tantalum Ta, and the coating is recorded as TaN X2 +Ta composite coating.
[0035] In a further embodiment, the metal tantalum Ta is in an α phase or a β phase. The metal tantalum Ta coating deposited at room temperature generally exhibits a tetragonal phase structure (β phase, ), the β-phase metal tantalum Ta coating has high hardness, but is very brittle, usually resulting in high coating stress. The thermodynamically stable phase of Ta is the bcc structure (α phase, ), high toughness and good ductility, is an ideal coating.
[0036] In a further embodiment, the total thickness of the coating is 0.5 to 200 μm.
[0037] In a second aspect, the present application provides a method for protecting the surface of a samarium cobalt permanent magnet material, comprising the following steps:
[0038] The coating in any of the above embodiments is deposited on the surface of the samarium cobalt permanent magnet material.
[0039] In a further embodiment, the coating is deposited by sputtering, ion plating or spraying.
[0040] A further solution is to clean the target material before sputtering, the working gas pressure is 0.1-5 Pa, and the sputtering power per unit target area is 0.1-15 W / cm 2 , cleaning time is greater than or equal to 1min.
[0041] In a further embodiment, during sputtering, the working gas pressure is 0.1-5 Pa, and the sputtering power per unit target area is 0.1-15 W / cm 2 , and apply a bias voltage of -400 to -1V.
[0042] A further solution is to clean the sputtering target material before sputtering, and to pickle, wash and dry the samarium cobalt permanent magnet material.
[0043] A further solution is to clean the target material for ion plating before ion plating, with a working gas pressure of 0.5-5 Pa and a current density per unit target area of 0.5-5 A / cm 2 , cleaning time is greater than or equal to 1min.
[0044] In a further embodiment, when ion plating is performed, the working gas pressure is 0.5 to 5 Pa, and the current density per unit target area is 0.5 to 5 A / cm 2 , and apply a bias voltage of -400 to -1V.
[0045] A further solution is to clean the ion plating target material before ion plating, and to pickle, wash and dry the samarium cobalt permanent magnet material.
[0046] Compared with the prior art, the coating of the present application has the following beneficial effects:
[0047] The present application provides a coating for surface protection of samarium cobalt permanent magnet materials, which can block the internal elements of the permanent magnet material from diffusing outward, and can also block the external O element from diffusing into the permanent magnet material, thereby improving the high temperature resistance of the samarium cobalt permanent magnet material and inhibiting the attenuation of the magnetic properties of samarium cobalt in a high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 Sm2Co with Ta coating 17 Structural diagram of a cross section of a permanent magnetic material.
[0049] Implementation Method
[0050] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0051] Example 1
[0052] The selected samarium cobalt permanent magnet materials are:
[0053] The first generation of rare earth permanent magnet material 1:5 samarium cobalt (sintered SmCo5), grade 22, is mainly composed of Sm (rare earth metal samarium), Pr (rare earth metal praseodymium), Co (metal cobalt). Sintered SmCo5 adopts powder sintering process, and the process flow can be summarized as smelting-powder making-molding-sintering-testing-processing.
[0054] The selected coatings are:
[0055] Ta coating, Ta is α phase.
[0056] The steps for depositing the coating are as follows:
[0057] (1) Two Ta targets (purity of 99.95%) were installed on the magnetron sputtering source in the vacuum chamber, and the angle between the Ta target and the horizontal plane of the sample turntable was adjusted to 45°.
[0058] (2) The samarium cobalt permanent magnet material is placed on the sample turntable after being pickled, washed with water and dried.
[0059] (3) Use a mechanical pump to pre-evacuate the vacuum chamber until the vacuum degree is less than 20 Pa, and then use a molecular pump to evacuate the vacuum chamber until the vacuum degree reaches 8.0×10- 4 Below Pa.
[0060] (4) Cleaning the Ta target under the following cleaning conditions: using Ar (purity of 99.999%) as the working gas, controlling the working gas pressure to 0.5 Pa, and the sputtering power per unit target area to 2 W / cm 2 , cleaning time is 30min.
[0061] (5) Sputtering deposition of samarium cobalt permanent magnet material, the deposition conditions are: using Ar (purity of 99.999%) as the working gas, controlling the working gas pressure to 0.5 Pa, and the sputtering power per unit target area to 4 W / cm 2 , apply a bias of -100 V, adjust the substrate temperature to 400°C with a built-in heater, and control the deposition thickness to 4 μm to deposit a Ta coating.
[0062] Example 2
[0063] The only difference from Example 1 is that the selected samarium cobalt permanent magnet material is:
[0064] The second generation of rare earth permanent magnet materials 2:17 Samarium Cobalt (sintered Sm2Co 17), brand 26H, composition: Sm (rare earth metal samarium), Co (metal cobalt), Cu (metal copper), Fe (metal iron), Zr (subgroup element zirconium). Sintered Sm2Co 17 The powder sintering process is adopted, and the process flow can be summarized as melting-powder making-molding-sintering-testing-processing.
[0065] Example 3
[0066] The selected samarium cobalt permanent magnet materials are:
[0067] The first generation of rare earth permanent magnet material 1:5 samarium cobalt (sintered SmCo5), grade 22, is mainly composed of Sm (rare earth metal samarium), Pr (rare earth metal praseodymium), Co (metal cobalt). Sintered SmCo5 adopts powder sintering process, and the process flow can be summarized as smelting-powder making-molding-sintering-testing-processing.
[0068] The selected coatings are:
[0069] Ta coating, Ta is α phase.
[0070] The steps for depositing the coating are as follows:
[0071] (1) Two Ta arc targets (purity of 99.95%) were installed on the arc source in the vacuum chamber.
[0072] (2) The samarium cobalt permanent magnet material is placed on the sample turntable after being pickled, washed with water and dried.
[0073] (3) Use a mechanical pump to pre-evacuate the vacuum chamber until the vacuum degree is less than 20 Pa, and then use a molecular pump to evacuate the vacuum chamber until the vacuum degree reaches 8.0×10- 4 Below Pa.
[0074] (4) Cleaning the Ta arc target under the following cleaning conditions: using Ar (purity of 99.999%) as the working gas, controlling the working gas pressure to 1 Pa, and the current density per unit target area to 1 A / cm 2 , cleaning time is 30min.
[0075] (5) Multi-arc deposition was performed on the SmCo permanent magnet material workpiece. The deposition conditions were: Ar (purity of 99.999%) was used as the working gas, the working gas pressure was controlled to be 1 Pa, and the current density per unit target area was 1 A / cm 2 , apply a bias voltage of -200 V, adjust the substrate temperature to 400°C with a built-in heater, and control the deposition thickness to ~8 μm, thereby depositing a Ta coating.
[0076] Example 4
[0077] The only difference from Example 3 is that the selected samarium cobalt permanent magnet material is:
[0078] The second generation of rare earth permanent magnet materials 2:17 Samarium Cobalt (sintered Sm2Co 17 ), brand 26H, composition: Sm (rare earth metal samarium), Co (metal cobalt), Cu (metal copper), Fe is metal iron, Zr (subgroup element zirconium). Sintered Sm2Co 17 The powder sintering process is adopted, and the process flow can be summarized as melting-powder making-molding-sintering-testing-processing.
[0079] Example 5
[0080] The selected samarium cobalt permanent magnet materials are:
[0081] The first generation of rare earth permanent magnet material 1:5 samarium cobalt (sintered SmCo5), grade 22, is mainly composed of Sm (rare earth metal samarium), Pr (rare earth metal praseodymium), Co (metal cobalt). Sintered SmCo5 adopts powder sintering process, and the process flow can be summarized as smelting-powder making-molding-sintering-testing-processing.
[0082] The selected coatings are:
[0083] T N X2 +Ta composite coating, Ta is α phase.
[0084] The steps for depositing the coating are as follows:
[0085] (1) Two Ta targets (purity of 99.95%) were installed on the magnetron sputtering source in the vacuum chamber, and the angle between the Ta target and the horizontal plane of the sample turntable was adjusted to 45°.
[0086] (2) The samarium cobalt permanent magnet material is placed on the sample turntable after being pickled, washed with water and dried.
[0087] (3) Use a mechanical pump to pre-evacuate the vacuum chamber until the vacuum degree is less than 20 Pa, and then use a molecular pump to evacuate the vacuum chamber until the vacuum degree reaches 8.0×10- 4 Below Pa.
[0088] (4) Cleaning the Ta target under the following cleaning conditions: using Ar (purity of 99.999%) as the working gas, controlling the working gas pressure to 0.5 Pa, and the sputtering power per unit target area to 2 W / cm 2 , cleaning time is 30min.
[0089] (5) Sputtering deposition was performed on the samarium cobalt permanent magnet material workpiece. The deposition conditions were: using Ar (purity of 99.999%) and N2 (purity of 99.999%) as working gases, controlling the working gas pressure to 0.5 Pa, and the deposition thickness to 0.1 μm, thereby depositing TaN X2It should be noted that there is no need to use an internal heater to regulate the substrate temperature.
[0090] (6) N2 is turned off, and Ar (purity of 99.999%) is used as the working gas, and the deposition thickness is controlled to be ∼3.9 μm, thereby depositing a Ta coating.
[0091] Example 6
[0092] The only difference from Example 5 is that the selected samarium cobalt permanent magnet material is:
[0093] The second generation of rare earth permanent magnet materials 2:17 Samarium Cobalt (sintered Sm2Co 17 ), brand 26H, composition: Sm (rare earth metal samarium), Co (metal cobalt), Cu (metal copper), Fe is metal iron, Zr (subgroup element zirconium). Sintered Sm2Co 17 The powder sintering process is adopted, and the process flow can be summarized as melting-powder making-molding-sintering-testing-processing.
[0094] Example 7
[0095] The selected samarium cobalt permanent magnet materials are:
[0096] The second generation of rare earth permanent magnet materials 2:17 Samarium Cobalt (sintered Sm2Co 17 ), the grade is high temperature resistant samarium cobalt T-550, the maximum operating temperature of this grade of samarium cobalt reaches 550℃, and the composition is: Sm (rare earth metal samarium), Co (metal cobalt), Cu (metal copper), Fe is metal iron, Zr (sub-group element zirconium). 17 The powder sintering process is adopted, and the process flow can be summarized as melting-powder making-molding-sintering-testing-processing.
[0097] Selected coating:
[0098] TaO X1 Plating.
[0099] The steps for depositing the coating are as follows:
[0100] (1) Two Ta targets (purity of 99.95%) were installed on the magnetron sputtering source in the vacuum chamber, and the angle between the Ta target and the horizontal plane of the sample turntable was adjusted to 45°.
[0101] (2) The samarium cobalt permanent magnet material is placed on the sample turntable after being pickled, washed with water and dried.
[0102] (3) Use a mechanical pump to pre-evacuate the vacuum chamber until the vacuum degree is less than 20 Pa, and then use a molecular pump to evacuate the vacuum chamber until the vacuum degree reaches 8.0×10- 4 Below Pa.
[0103] (4) Cleaning the Ta target under the following cleaning conditions: using Ar (purity of 99.999%) as the working gas, controlling the working gas pressure to 0.5 Pa, and the sputtering power per unit target area to 2 W / cm 2 , cleaning time is 30min.
[0104] (5) Sputtering deposition was performed on the samarium cobalt permanent magnet material workpiece. The deposition conditions were: using Ar (purity of 99.999%) and O2 (purity of 99.999%) as working gases, controlling the working gas pressure to 0.5 Pa, and depositing a thickness of 2 μm, thereby depositing TaO X1 It should be noted that there is no need to use an internal heater to regulate the substrate temperature.
[0105] Example 8
[0106] The only difference from Example 7 is that the selected samarium cobalt permanent magnet material is:
[0107] The second generation of rare earth permanent magnet materials 2:17 Samarium Cobalt (sintered Sm2Co 17 ), grade 26H, the composition is: Sm (rare earth metal samarium), Co (metal cobalt), Cu (metal copper), Fe is metal iron, Zr (sub-group element zirconium). Sintered Sm2Co with grade 26H 17 The powder sintering process is adopted, and the process flow can be summarized as melting-powder making-molding-sintering-testing-processing.
[0108] Example 9
[0109] The selected samarium cobalt permanent magnet materials are:
[0110] The first generation of rare earth permanent magnet material 1:5 samarium cobalt (sintered SmCo5), grade 22, is mainly composed of Sm (rare earth metal samarium), Pr (rare earth metal praseodymium), Co (metal cobalt). Sintered SmCo5 adopts powder sintering process, and the process flow can be summarized as smelting-powder making-molding-sintering-testing-processing.
[0111] The selected coatings are:
[0112] TaNb binary alloy coating.
[0113] The steps for depositing the coating are as follows:
[0114] (1) Two TaNb binary alloy targets (50 at% Ta: 50 at% Nb, purity 99.95%) were mounted on a sputtering source in a vacuum chamber, and the angle between the TaNb binary alloy target and the horizontal plane of the sample turntable was adjusted to 45°.
[0115] (2) The samarium cobalt permanent magnet material is placed on the sample turntable after being pickled, washed with water and dried.
[0116] (3) Use a mechanical pump to pre-evacuate the vacuum chamber until the vacuum degree is less than 20 Pa, and then use a molecular pump to evacuate the vacuum chamber until the vacuum degree reaches 8.0×10- 4 Below Pa.
[0117] (4) Cleaning the TaNb binary alloy target under the following cleaning conditions: using Ar (purity of 99.999%) as the working gas, controlling the working gas pressure to 0.5 Pa, and the sputtering power per unit target area to 2 W / cm 2 , cleaning time is 30min.
[0118] (5) Sputtering deposition of samarium cobalt permanent magnet material, the deposition conditions are: using Ar (purity of 99.999%) as the working gas, controlling the working gas pressure to 0.5 Pa, and the sputtering power per unit target area to 4 W / cm 2 , apply a bias voltage of -100 V, heat the substrate temperature to 400°C with a built-in heater, and control the deposition thickness to 4 μm, thereby depositing a TaNb binary alloy coating.
[0119] Example 10
[0120] The only difference from Example 9 is that the selected samarium cobalt permanent magnet material is:
[0121] The second generation of rare earth permanent magnet materials 2:17 Samarium Cobalt (sintered Sm2Co 17 ), brand 26H, composition: Sm (rare earth metal samarium), Co (metal cobalt), Cu (metal copper), Fe (metal iron), Zr (subgroup element zirconium). Sintered Sm2Co 17 The powder sintering process is adopted, and the process flow can be summarized as melting-powder making-molding-sintering-testing-processing.
[0122] Test Example 1
[0123] The SmCo5 permanent magnet material with Ta coating of Example 1 and the Sm2Co5 permanent magnet material with Ta coating of Example 2 17 Permanent magnetic material, corresponding SmCo5 permanent magnetic material without any coating (recorded as comparative example 1), corresponding Sm2Co 17 The permanent magnetic material (referred to as comparative example 2) was subjected to isothermal heat treatment at 500°C in an air environment, and then the magnetic properties before and after the heat treatment were tested using a vibrating sample magnetometer (VSM). The results are shown in the following table:
[0124]
[0125] The SmCo5 permanent magnet material with Ta coating of Example 1 and the SmCo5 permanent magnet material with Ta coating of Example 217 After the permanent magnet material was heat treated at 500℃ for 192 hours in an oxygen environment, the remanence (Br) decreased by -23.24% and 15.10%, respectively. The SmCo5 permanent magnet material without any coating in Comparative Example 1 was powdered, and the SmCo5 permanent magnet material without any coating in Comparative Example 2 was 17 The remanence of the permanent magnet material decreased by 64.16%. It can be seen that the Ta coating has an obvious high-temperature protection effect on the SmCo permanent magnet material. The reason is that the dense Ta coating inhibits the outward diffusion of Sm and the inward diffusion of O, prevents the formation of a surface aging layer, and reduces the loss of magnetic properties.
[0126] Test Example 2
[0127] The SmCo5 permanent magnet material with Ta coating of Example 3 and the Sm2Co5 permanent magnet material with Ta coating of Example 4 17 The permanent magnetic material is subjected to isothermal heat treatment at 500°C in air environment. The magnetic properties before and after heat treatment are then tested using a vibrating sample magnetometer (VSM). The results are shown in the following table:
[0128]
[0129] The SmCo5 permanent magnet material with Ta coating of Example 3 and the SmCo5 permanent magnet material with Ta coating of Example 4 17 After the permanent magnet material was heat treated at 500℃ for 192 hours in an oxygen environment, the remanence (Br) decreased by 19.32% and 10.58% respectively, while the SmCo5 permanent magnet material without any coating in Comparative Example 1 was pulverized, and the SmCo5 permanent magnet material without any coating in Comparative Example 2 was 17 The remanence of the permanent magnet material decreased by 64.16%. It can be seen that the Ta coating has an obvious high-temperature protection effect on the SmCo permanent magnet material. The reason is that the dense Ta coating inhibits the outward diffusion of Sm and the inward diffusion of O, prevents the formation of a surface aging layer, and reduces the loss of magnetic properties.
[0130] In addition, compared with the Ta coating in Example 1 and Example 2, the Ta coating in Example 3 and Example 4 has better high-temperature protection effect on the samarium cobalt permanent magnet material. The reason is that Example 3 and Example 4 use multi-arc ion plating to deposit the Ta coating, which has two changes compared with Example 1 and Example 2. First, the thickness is increased by 1 times to 8μm, and second, the density of the coating is improved by applying a negative bias. The above two changes make the Ta coating have a better protection effect.
[0131] Test Example 3
[0132] For the TaN X2+Ta composite coating of SmCo5 permanent magnet material, Example 6 with TaN X2 +Ta composite coating of Sm2Co 17 The permanent magnetic material is subjected to isothermal heat treatment at 500°C in air environment. The magnetic properties before and after heat treatment are then tested using a vibrating sample magnetometer (VSM). The results are shown in the following table:
[0133]
[0134] Example 5 having TaN X2 +Ta composite coating of SmCo5 permanent magnet material and the TaN X2 +Ta composite coating of Sm2Co 17 After the permanent magnet material was heat treated at 500℃ for 192 hours in an oxygen environment, the remanence (Br) decreased by 22.44% and 14.54%, respectively. The SmCo5 permanent magnet material without any coating in Comparative Example 1 was pulverized, and the SmCo5 permanent magnet material without any coating in Comparative Example 2 was 17 The remanence of the permanent magnet material decreased by 64.16%, so it can be seen that TaN X2 +Ta composite coating improves the high temperature stability of samarium cobalt permanent magnet materials. The reason is that through the dense TaN X2 +Ta composite coating inhibits the outward diffusion of Sm and the inward diffusion of O.
[0135] In addition, compared with the Ta plating in Example 1 and Example 2, the TaN in Example 5 and Example 6 X2 +Ta composite coating has better high temperature protection effect on samarium cobalt permanent magnet material, because TaN X2 The structure of TaN coating is different from that of Ta coating. X2 The interface between the coating and the Ta coating forms a more effective diffusion barrier, which improves the inhibition of O and Sm diffusion. X2 The coating can be used as an induction layer, which can induce the Ta coating to form an α-phase structure at room temperature, so that the Ta coating has better protection effect and higher bonding strength.
[0136] Test Example 4
[0137] For the TaO X1 Sm2Co coating 17 The permanent magnetic material and the corresponding high temperature resistant samarium cobalt permanent magnetic material without any coating (recorded as comparative example 3) were subjected to isothermal heat treatment under the conditions of 500°C in air environment, and then the magnetic properties before and after the heat treatment were tested using a vibrating sample magnetometer (VSM). The results are shown in the following table:
[0138]
[0139] Example 7 with TaO X1 The coating is Sm2Co with grade T-550 17 Permanent magnetic material and the TaO X1 The coating is Sm2Co with grade 26H 17 After the permanent magnet material was heat treated at 500℃ for 192 hours in an oxygen environment, the remanence (Br) decreased by 2.94% and 5.45% respectively. 17 Permanent magnetic material and Sm2Co26H without any coating of comparative example 2 17 The remanence of permanent magnet materials decreased by 48.91% and 64.16% respectively. It can be seen that TaO X1 The coating significantly improves the high temperature stability of samarium cobalt permanent magnet materials. The reason is that through the dense TaO X1 The coating inhibits the outward diffusion of Sm and the inward diffusion of O.
[0140] In addition, compared with the Ta plating in Example 2, the Ta plating in Example 4, and the TaN in Example 6, X2 +Ta composite coating compared to the TaO X1 The coating has a better high temperature protection effect on samarium cobalt permanent magnet materials because TaO X1 The coating is in a stable oxide state, so TaO X1 The coating no longer reacts with O in the air, making TaO X1 The coating has excellent anti-oxidation performance. X1 The coating will not fall off due to re-oxidation in the air, making TaO X1 Always have a stable protection effect.
[0141] Test Example 5
[0142] The SmCo5 permanent magnet material with TaNb coating of Example 9 and the Sm2Co5 permanent magnet material with TaNb coating of Example 10 are 17 The permanent magnetic material is subjected to isothermal heat treatment at 500°C in air environment. The magnetic properties before and after heat treatment are then tested using a vibrating sample magnetometer (VSM). The results are shown in the following table:
[0143]
[0144] The SmCo5 permanent magnet material with TaNb coating of Example 9 and the SmCo5 permanent magnet material with TaNb coating of Example 10 17After the permanent magnet material was heat treated at 500℃ for 192 hours in an oxygen environment, the remanence (Br) decreased by 17.90% and 8.9%, respectively. The SmCo5 permanent magnet material without any coating in Comparative Example 1 was pulverized, and the SmCo5 permanent magnet material without any coating in Comparative Example 2 was 17 The remanence of the permanent magnet material decreased by 64.16%. It can be seen that the TaNb coating has an obvious high-temperature protection effect on the samarium cobalt permanent magnet material. The reason is that the sputtering yields of Ta and Nb are similar, the deposited TaNb coating does not have much component segregation, and Ta and Nb can form a denser coating than Ta, which can effectively inhibit the outward diffusion of Sm and the inward diffusion of O, prevent the formation of a surface aging layer, and reduce the loss of magnetic properties.
[0145] Test Example 6
[0146] 6.1 When other conditions are the same as those in Example 2, the effect of the working gas pressure for sputtering on the magnetic properties of the permanent magnetic material with a coating is investigated. The investigation method is similar to that of Experimental Example 1. The results are shown in the following table:
[0147]
[0148] It can be seen from the table above that when the working pressure is 0.1-5 Pa, the magnetic property loss after high temperature aging is reduced while ensuring sputtering. When the working pressure is too low, sputtering is impossible. When the working pressure is too high, the density of the coating decreases and the protective performance decreases.
[0149] 6.2 When other conditions are the same as those in Example 2, the effect of the sputtering power per unit target area for sputtering plating on the magnetic properties of the permanent magnetic material with a coating is investigated. The investigation method is similar to that of Experimental Example 1. The results are shown in the following table:
[0150]
[0151]
[0152] It can be seen from the table above that the sputtering power per unit target area is 0.1 to 15 W / cm 2 When the sputtering power is too low, sputtering is impossible. When the sputtering power is too high, the grains are coarse and the protective performance of the coating is reduced.
[0153] 6.3 When other conditions are the same as those in Example 2, the effect of cleaning time for sputtering plating on the magnetic properties of the permanent magnetic material with a coating is investigated. The investigation method is similar to that of Experimental Example 1. The results are shown in the following table:
[0154]
[0155] It can be seen from the above table that when the cleaning time is greater than or equal to 1 min, the coating quality is improved and the magnetic property loss after high-temperature aging is reduced.
[0156] 6.4 When other conditions are the same as those in Example 2, the effect of the bias voltage for sputtering on the magnetic properties of the permanent magnetic material with the coating is investigated. The investigation method is similar to that of Experimental Example 1. The results are shown in the following table:
[0157]
[0158]
[0159] It can be seen from the above table that when the bias voltage is -400 to -1V, the magnetic property loss after high temperature aging is reduced.
[0160] 6.5 When other conditions are the same as those in Example 4, the effect of the working gas pressure for ion plating on the magnetic properties of the permanent magnetic material with a coating is investigated. The investigation method is similar to that of Experimental Example 2. The results are shown in the following table:
[0161]
[0162] It can be seen from the above table that when the working gas pressure is 0.5~5Pa, while ensuring ion plating, the magnetic property loss after high temperature aging is reduced.
[0163] 6.6 When other conditions are the same as those in Example 4, the effect of the current density per unit target area for ion plating on the magnetic properties of the permanent magnetic material with a coating is investigated. The investigation method is similar to that of Experimental Example 2. The results are shown in the following table:
[0164]
[0165]
[0166] It can be seen from the table above that the current density per unit target area is 0.5 to 5 A / cm 2 When the magnetic properties are reduced after high temperature aging.
[0167] 6.7 When other conditions are the same as those in Example 4, the effect of the cleaning time for ion plating on the magnetic properties of the permanent magnetic material with the coating is investigated. The investigation method is similar to that of Experimental Example 2. The results are shown in the following table:
[0168]
[0169] It can be seen from the above table that when the cleaning time is greater than or equal to 1 min, the magnetic property loss after high temperature aging is reduced.
[0170] 6.8 When other conditions are the same as those in Example 4, the effect of the bias voltage for ion plating on the magnetic properties of the permanent magnetic material with a coating is investigated. The investigation method is similar to that of Experimental Example 2. The results are shown in the following table:
[0171]
[0172] It can be seen from the above table that when the bias voltage is -400 to -1V, the magnetic property loss after high temperature aging is reduced.
[0173] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A coating for surface protection of samarium cobalt permanent magnet material, characterized in that: Includes at least one of the following ingredients: Tantalum Oxide TaO X1 , X1 is any number between 0 and 2.5; Tantalum Nitride TaN X2 , X2 is any number between 0 and 1.6; An alloy comprising metal tantalum Ta and metal M, wherein M comprises at least one of V, Nb, Zr, Hf, Cr, Al, and Ni; The coating comprises two or more layers, each of which is stacked, and each of which comprises one of the following components: Tantalum Oxide TaO X1 , X1 is any number between 0 and 2.5; Tantalum Nitride TaN X2 , X2 is any number between 0 and 1.6; An alloy comprising metal tantalum Ta and metal M, wherein M is at least one of V, Nb, Zr, Hf, Cr, Al, and Ni.
2. The coating according to claim 1, characterized in that The metal tantalum Ta is in α phase or β phase.
3. The coating according to claim 1, characterized in that The thickness of the coating is 0.5-200 μm.
4. A method for protecting the surface of a samarium cobalt permanent magnet material, characterized in that: The following steps are involved: The coating according to any one of claims 1 to 3 is deposited on the surface of the samarium cobalt permanent magnet material.
5. The protection method according to claim 4, characterized in that: The coating is deposited by sputtering, ion plating or spraying.
6. The protection method according to claim 5, characterized in that: Before the sputtering, the target material is cleaned, the working pressure is 0.1-5 Pa, and the sputtering power per unit target area is 0.1-15 W / cm 2 , cleaning time is greater than or equal to 1min.
7. The protection method according to claim 5, characterized in that: During the sputtering process, the working gas pressure is 0.1-5 Pa, and the sputtering power per unit target area is 0.1-15 W / cm 2 , and apply a bias voltage of -400 to -1V.
8. The protection method according to claim 5, characterized in that: Before the ion plating, the target material for the ion plating is cleaned, the working gas pressure is 0.5-5 Pa, and the current density per unit target area is 0.5-5 A / cm 2 , cleaning time is greater than or equal to 1min.
9. The protection method according to claim 5, characterized in that: When the ion plating is performed, the working gas pressure is 0.5-5 Pa, and the current density per unit target area is 0.5-5 A / cm 2 , and apply a bias voltage of -400 to -1V.
Citation Information
Patent Citations
Manufacturing method of high-temperature cobalt-based permanent magnet materials
CN103280289A
Ta-W-Nb-Al-Cr-Ti-Si series high-entropy alloy diffusion coating for high-throughput screening and preparation method of Ta-W-Nb-Al-Cr-Ti-Si series high-entropy alloy diffusion coating
CN111876645A
Method and composite for protection of thermal barrier coating with an impermeable barrier coating
WO1996031687A1